Pengaruh Metode Ekstraksi Daun Jarak Cina (Jatropha multifida L.) Secara Maserasi dan Microwave-Assisted Extraction (MAE) Terhadap Aktivitas Antijamur Pada Candida albicans - Aryunda, Divia; Nasution, Muhammad Amin; Nasution, Haris Munandar; Pulungan , Ainil Fithri (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Introduction: Indonesia possesses high biodiversity, including the Jatropha multifida L. plant, which contains secondary metabolites with potential antimicrobial properties. Traditionally, the leaves of Jatropha multifida have been used as herbal medicine, particularly for inhibiting the growth of microorganisms. Objective: This study aims to determine the total flavonoid content in the ethanol extract of Jatropha multifida leaves and to compare the effectiveness of two extraction methods, maceration and Microwave-Assisted Extraction (MAE), in inhibiting the growth of Candida albicans. Methods: The research stages included the characterization of the powdered simplicia, extraction of Jatropha multifida leaves using 96% ethanol by maceration and MAE methods, and phytochemical screening. The total flavonoid content was determined using UV-Vis spectrophotometry at a wavelength of 431 nm. Antifungal activity against Candida albicans was tested for each extract at specific concentrations. Results: The ethanol extract obtained through maceration showed a total flavonoid content of 34.7089 ± 0.1206 mg QE/g, while the MAE method yielded 32.1923 ± 0.1113 mg QE/g. The highest antifungal activity was observed in the MAE extract at a 75% concentration, producing an inhibition zone of 24.7 mm. The maceration extract at the same concentration produced an inhibition zone of 23.7 mm. As a positive control, 2% ketoconazole resulted in an inhibition zone of 31.4 mm. Conclusion: Although the maceration method produced a higher total flavonoid content, the extract obtained through the MAE method demonstrated more potent antifungal activity against Candida albicans at the same concentration.